Evaluation of the antibacterial activity of Elsholtzia ciliate essential oil against halitosis-related Fusobacterium nucleatum and Porphyromonas gingivalis - Li, Fengjiao; Wang, Chuandong; Xu, Jing; Wang, Xiaoyu; Cao, Meng; Wang, Shuhua; Zhang, Tingting; Xu, Yanyong; Wang, Jing; Pan, Shaobin; Hu, Wei (Frontiers in Microbiology, 2023)
The broad-spectrum antimicrobial activity of Elsholtzia ciliate essential oil (ECO) has been previously reported, but its effectiveness against halitosis-causing bacteria such as Fusobacterium nucleatum and Porphyromonas gingivalis is not well understood. In this study, we investigated the bacteriostatic activity of ECO against planktonic cells and biofilms of F. nucleatum and P. gingivalis, as well as its ability to inhibit bacterial metabolism and production of volatile sulfur compounds (VSCs) at sub-lethal concentrations. Our findings revealed that ECO exhibited comparable activities to chlorhexidine against these oral bacteria. Treatment with ECO significantly reduced the production of VSCs, including hydrogen sulfide, dimethyl disulfide, and methanethiol, which are major contributors to bad breath. As the major chemical components of ECO, carvacrol, p-cymene, and phellandrene, were demonstrated in vitro inhibitory effects on F. nucleatum and P. gingivalis, and their combined use showed synergistic and additive effects, suggesting that the overall activity of ECO is derived from the cumulative or synergistic effect of multiple active components. ECO was found to have a destructive effect on the bacterial cell membrane by examining the cell morphology and permeability. Furthermore, the application of ECO induced significant changes in the bacterial composition of saliva-derived biofilm, resulting in the elimination of bacterial species that contribute to halitosis, including Fusobacterium, Porphyromonas, and Prevotella. These results provide experimental evidence for the potential clinical applications of ECOs in the prevention and treatment of halitosis.